“Beralas Bumi Beratap Langit”: An Investigation of Creating Role and Space through Site-Specific - ABDUR RIZKY AKBAR (Mudra Jurnal Seni Budaya, 2022)
This article is devoted to the analysis of theatre performances “Beralas Bumi Beratap Langit” which uses a site-specific  method. Central to the site-specific approach is concern to the potential of unconventional spaces. The site-specific approach seeks to use the unique landscape properties of the site, locations selected based on their ability to amplify storytelling and form a clearer background for the actors in a theatrical production. This approach in theatre studies, especially with regard to actors and spaces, seems to offer breadth and bridges to the creating role and the flexibility which many representations come together, site-specific is then used as a method that helps in achieving character through learning and creating acting, from the Covid-19 pandemic intervention which changed at least most of the methods in learning acting and other creative processes. This article aims to investigate a site-specific approach that is personalized in the interest of providing insight or catalysts on the mode of acting and actors as subjects in theatrical performances. Using the ethnographic method, data were obtained on the creative process during the preparation of the show by the “Panggung Bercerita” theatre community. Practical investigation of a site-specific approach to the theatre stage method yields the following conclusions: 1) natural sets create an atmosphere of intimacy, 2) helps actors feel immersion into the world being played, and 3) provides rich and culturally relevant visualizations of the actor's image.